Analisis Sistem Informasi Data Penjualan Barang Komputer Menggunakan Metode Agile Berbasis Web - Muhammad Azriel; Fajri Maulana Azzam Harahap (PT Jurnal Cendekia Indonesia, 2025)
This research investigates the development of a web-based information system for the sale of computer goods using the Agile method. The system is designed to organize transactions, product data, customers, and suppliers in a structured manner and in real time. By leveraging the iterative approach inherent in Agile, development is carried out incrementally through sprints, allowing for rapid adjustments to user needs. Blackbox testing results indicate that most features function as expected, although there are some minor shortcomings in input validation. The system has proven to enhance operational efficiency as well as the accuracy of sales reporting. These findings support the use of Agile methods for sales systems that are small to medium scale and require flexibility and speed in adaptation